2020
DOI: 10.1111/csp2.306
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The sensory ecology of fear: African elephants show aversion to olfactory predator signals

Abstract: The outcomes of human-elephant conflict range from expensive to fatal to both humans and elephants across Africa and Asia, which has prompted extensive efforts to mitigate it. Previous attempts have focused primarily on physical barriers, plant deterrent compounds, and elephant-nuisance species. However, the handful of effective approaches are expensive and maintenance-intensive. Here, we approach the problem from the perspective of the sensory ecology of fear, and demonstrate elephant aversion to olfactory si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Numerous studies have reported the importance of olfactory cues for social communication and food selection in Asian and savanna elephants, and that their sense of smell may play an important role in physical and social decision-making [28][29][30][31]. While olfactory behavioural choice experiments have been performed with both savanna and Asian elephants [32][33][34][35][36][37][38], there have been no studies comparing the olfactory abilities of the two species. This is surprising considering the importance of olfaction for both species of elephants.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the importance of olfactory cues for social communication and food selection in Asian and savanna elephants, and that their sense of smell may play an important role in physical and social decision-making [28][29][30][31]. While olfactory behavioural choice experiments have been performed with both savanna and Asian elephants [32][33][34][35][36][37][38], there have been no studies comparing the olfactory abilities of the two species. This is surprising considering the importance of olfaction for both species of elephants.…”
Section: Introductionmentioning
confidence: 99%